DAYA PRAGMATIK (PRAGMATIK FORCE) PADA PERBANDINGAN ANTONIM BAHASA JAWA DAN BAHASA INDONESIA SERTA KORELASI BUDAYA MASYARAKAT PENUTURNYA - Safitri, Paramita Ida; Puspitasari, Rosika Herwin (PRASASTI: Journal of Linguistics, 2016)
The meaning of antonyms are simply the words of opposites, antonyms are divided into four kinds namely; (a) absolute, (b) gradation, (c) hierarchical, (d) reciprocal. Antonyms comparative study on Javanese and Indonesian language through study aims to determine the pragmatic force sequence patterns found on speakers of Javanese and Indonesian, to appraise the values contained in the philosophy of speech acts activities, among speakers of Javanese and Indonesian. The data used in this study apart from information obtained from the book of antonyms collection contained in Javanese and Indonesian were also correlated in the application of the usual conversation by speakers of Javanese and Indonesian. The method used in this research through a comparative study done by comparing the antonym that is customarily used by speakers of Javanese and Indonesian speakers. The result of this study showed that the antonyms contained in Javanese and Indonesian language have different sequence patterns, this is due to the differences in cultural bacground contained in the community of Javanese and Indonesian speaker.Keywords: pragmatic force, comparison, antonyms Javanese, Indonesian antonyms, cultural speech community.